The effects of omega-3 fatty acids and vitamin E co-supplementation on gene expression of lipoprotein(a) and oxidized low-density lipoprotein, lipid profiles and biomarkers of oxidative stress in patients with polycystic ovary syndrome. (5th January 2017) - Rahmani, Elham; Samimi, Mansooreh; Ebrahimi, Faraneh Afshar; Foroozanfard, Fatemeh; Ahmadi, Shahnaz; Rahimi, Maryam; Jamilian, Mehri; Aghadavod, Esmat; Bahmani, Fereshteh; Taghizadeh, Mohsen; Memarzadeh, Mohammad Reza; Asemi, Zatollah
Abstract: This study was conducted to determine the effects of omega-3 fatty acids and vitamin E co-supplementation on gene expression of lipoprotein(a) (Lp[a]) and oxidized low-density lipoprotein (Ox-LDL), lipid profiles and biomarkers of oxidative stress in women with polycystic ovary syndrome (PCOS). This randomized double-blind, placebo-controlled trial was done on 68 women diagnosed with PCOS according to the Rotterdam criteria aged 18–40 years old. Participants were randomly assigned into two groups to receive either 1000 mg omega-3 fatty acids from flaxseed oil containing 400 mg α-Linolenic acid plus 400 IU vitamin E supplements (n = 34) or placebo (n = 34) for 12 weeks. Lp(a) and Ox-LDL mRNA levels were quantified in peripheral blood mononuclear cells of PCOS women with RT-PCR method. Lipid profiles and biomarkers of oxidative stress were quantified at the beginning of the study and after 12-week intervention. Quantitative results of RT-PCR demonstrated that compared with the placebo, omega-3 fatty acids and vitamin E co-supplementation downregulated expressed levels of Lp(a) mRNA (P < 0.001) and Ox-LDL mRNA (P < 0.001) in peripheral blood mononuclear cells of women with PCOS. In addition, compared to the placebo group, omega-3 fatty acids and vitamin E co-supplementation resulted in a significant decrease in serum triglycerides (−22.1 ± 22.3 vs. +7.7 ± 23.6 mg/dL, P < 0.001), VLDL- (−4.4 ± 4.5 vs. +1.5 ± 4.7 mg/dL, P < 0.001), total- (−20.3 ± 16.6 vs. +12.2 ± 26.1 mg/dL, P < 0.001), LDL- (−16.7 ± 15.3 vs. +11.9 ± 26.1 mg/dL, P < 0.001) and total-/HDL-cholesterol (−0.5 ± 0.6 vs. +0.4 ± 0.8, P < 0.001). There were a significant increase in plasma total antioxidant capacity (+89.4 ± 108.9 vs. +5.9 ± 116.2 mmol/L, P = 0.003) and a significant decrease in malondialdehyde levels (−0.3 ± 0.4 vs. -0.008 ± 0.6 μmol/L, P = 0.01) by combined omega-3 fatty acids and vitamin E intake compared with the placebo group. Overall, omega-3 fatty acids and vitamin E co-supplementation for 12 weeks in PCOS women significantly improved gene expression of Lp(a) and Ox-LDL, lipid profiles and biomarkers of oxidative stress. Highlights: This study has evaluated the effects of omega-3 plus vitamin E intake in PCOS women. Co-supplementation in PCOS women had beneficial effects on lipid concentrations. Co-supplementation in PCOS women improved gene expression.